Environmental Health-Based Post-Coal Mine Policy in East Borneo - Absori, Absori; Yulianingrum, Aulia Vivi; Dimyati, Khudzaifah; Harun, Harun; Budiono, Arief; Disemadi, Hari Sutra (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Post-coal mine activities must be carried out by considering good management principles, to avoid negative environmental impacts, especially to avoid land surface imbalance, to avoid destruction of flora and fauna, and more importantly, to maintain the public health. The post-mining regulations based on the priorities of public health and environmental sustainability are designed to increase the human resource quality for the interests of regional development. AIM: This study aims to describe the post-coal mine policy in East Borneo and to formulate the post-coal mine policy as a form of control over ex-mine land from the aspect of environmental health. METHODS: This study uses the qualitative research design. It is a sociolegal type of research with the case study approach toward the currently developing post-coal mine reclamation. This study uses the fishbone analysis. RESULTS: The results of this research show that the supervision toward the ex-mines is still weak. It leads to expanding environmental destruction and some of the companies’ ignorance toward reclamation and post-mining obligations. This condition impacts the water quality, as it is the people’s necessity in fulfilling their basic needs. CONCLUSION: There needs to be a post-coal mine regulation through policies which prioritize environmental sustainability and public health. It includes the optimization of the ex-mine supervision, new regulations as the implementation of the central government’s constitutional regulation, and inspection of environmental health in achieving quality human resources of the region.